Health benefits of hormonal contraception used by symptoms associated with acne vulgaris and hirsutism - Anna Sobstyl; Zuzanna Chilimoniuk; Aleksandra Chałupnik; Magdalena Łakota-Sipa; Maciej Dobosz; Aleksandra Borkowska; Małgorzata Sobstyl (Kazimierz Wielki University, 2019)
Hormonal contraception in reproductive age is used not only as a birth control method but also for other indications like acne vulgaris and hirsutism. Acne vulgaris and hirsutism are important signs related to hyperandrogenaemia and provide a serious medical problem for the patients. Reduction of numerous existing symptoms leads to an improvement in the quality of women's life. The aim of the study is to present author's statistical data and to compare it to available data on non-contraceptive benefits.